2003
DOI: 10.1139/z03-184
|View full text |Cite
|
Sign up to set email alerts
|

Lizard community structure across a grassland – creosote bush ecotone in the Chihuahuan Desert

Abstract: I investigated the distribution and abundance of lizard species (Aspidoscelis inornatus, Aspidoscelis tesselatus, Aspidoscelis tigris, Aspidoscelis uniparens, Cophosaurus texanus, Crotaphytus collaris, Eumeces obsoletus, Gambelia wislizenii, Holbrookia maculata, Phrynosoma cornutum, Sceloporus magister, and Uta stansburiana) across a desert grassland – creosote bush (Larrea tridentata) ecotone in Dona Ana County, New Mexico. The ecotonal area in the Jornada del Muerto basin has increased dramatically in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
11
0
1
Order By: Relevance
“…At a similar grazing exclosure also in southeastern Arizona, where there is a cross-fence difference in vegetation, Bock et al (1990) found the lizard Sceloporus scalaris to be less abundant outside the livestock exclosure; the authors posited increased predation due to decreased vegetation complexity was responsible for the disparity. Another study in similar Chihuahuan desert habitat in southwestern New Mexico also posited that changes in lizard abundance across a gradient of vegetation complexity were due to variation in predation (Menke, 2003). Therefore we used one-tailed binomial tests to compare cross-fence relative number of tail-breaks for each species.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…At a similar grazing exclosure also in southeastern Arizona, where there is a cross-fence difference in vegetation, Bock et al (1990) found the lizard Sceloporus scalaris to be less abundant outside the livestock exclosure; the authors posited increased predation due to decreased vegetation complexity was responsible for the disparity. Another study in similar Chihuahuan desert habitat in southwestern New Mexico also posited that changes in lizard abundance across a gradient of vegetation complexity were due to variation in predation (Menke, 2003). Therefore we used one-tailed binomial tests to compare cross-fence relative number of tail-breaks for each species.…”
Section: Article In Pressmentioning
confidence: 99%
“…Mechanisms that may produce this relationship include increases in niche separation (Schoener, 1974;Fischer et al, 2004), variation in prey abundance (Vitt and Ohmart, 1977) and variation in predation risk (Bock et al, 1990;Menke, 2003). However, we do not know of any empirical tests of either the prey abundance or predation mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…Groups of gecko migrated between islands through human activity (Jesus et al 2001). Human activity leads to vegetation changes and trigger migration of Geckonidae species (Menke 2003). In Florida, acceleration in the population of invasive H. garnotii could replace the native species (H. tursicus) (Meshaka 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We expect riparian associates including checkered gartersnake, blacknecked gartersnake, desert spiny lizard (Menke 2003;Vitt and others 1981), Chihuahuan spotted lizards (Catron and others 2008), and checkered whiptail to be negatively impacted by declines of associated habitat. Coachwhips, though they depend on open grasslands and thick clumps of vegetation, also are reported to be sensitive to fragmentation (Mitrovich and others 2009), and we considered this species likely to experience disruption to their preferred habitat with potential negative effects on population size.…”
Section: Vegetation Associationmentioning
confidence: 99%